2023
DOI: 10.1002/cmdc.202200701
|View full text |Cite
|
Sign up to set email alerts
|

Terpyridine Glycoconjugates and Their Metal Complexes: Antiproliferative Activity and Proteasome Inhibition

Abstract: Metal terpyridine complexes have gained substantial interest in many application fields, such as catalysis and supramolecular chemistry. In recent years, the biological activity of terpyridine and its metal complexes has aroused considerable regard. On this basis, we synthesised new terpyridine derivatives of trehalose and glucose to improve the water solubility of terpyridine ligands and target them in cancer cells through glucose transporters. Glucose derivative and its copper(II) and iron(II) complexes show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
3
1
0
Order By: Relevance
“…Inorganics 2024, 12, x FOR PEER REVIEW 7 of 12 derivatives. Similar behavior has been proven for iron and copper complexes of TpyGlc and HAtpy [42,52].…”
Section: Antiproliferative Activity Of Pt-containing Complexessupporting
confidence: 79%
See 3 more Smart Citations
“…Inorganics 2024, 12, x FOR PEER REVIEW 7 of 12 derivatives. Similar behavior has been proven for iron and copper complexes of TpyGlc and HAtpy [42,52].…”
Section: Antiproliferative Activity Of Pt-containing Complexessupporting
confidence: 79%
“…However, data suggested that the presence of hydrophilic substituents in the tpy moiety leads to a considerable decrease in activity, as in the case of Glc and HA derivatives. Similar behavior has been proven for iron and copper complexes of TpyGlc and HAtpy [42,52].…”
Section: Uv-vis Spectroscopysupporting
confidence: 79%
See 2 more Smart Citations